Originality of creative work of women publicists of the Kyzylorda region - Yermaganbetova З.Н. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2020)
In the history of Kazakh journalism, women’s journalism has a special place. The beginning of the research activities of the first publicists Nazipa Kulzhanova, Sarah Esova, Nagima Arykova, Akkagaz Doszhanova, Mariam Seydalina was laid in the years of their journalistic activities. This article discusses the development of women’s journalism in the Syr region, traces the creative path of women journalists who have worked in print media, on television and who have contributed to the development of journalism in the region for many years. The article also discusses issues related to information management. The author of the article notes that these problems are the subject of his further research